2003
DOI: 10.1093/brain/awg010
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency at the  -synuclein gene underlies phenotypic severity in familial Parkinson's disease

Abstract: To date, two point mutations, G209A and G88C, have been reported in the coding region of the alpha-synuclein gene in autosomal dominant familial Parkinson's disease. When translated, these lead to the missense mutations Ala53Thr and Ala30Pro, respectively. Reduced mRNA expression of the G209A allele was reported recently in a Greek-American family. Here, we show that alpha-synuclein mRNA is normally expressed in blood cells and report the results of an analysis of alpha-synuclein mRNA and protein expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…When translated, these lead to the missense mutations Ala53Thr and Ala30Pro, respectively. Recently, reduced mRNA expression of the G209A allele was reported in a Greek-American family [23]. Very recently, we reported that the mRNA expression of the mutant G88C and G209A alleles of the α-synuclein gene is significantly reduced relative to the wild-type allele in lymphoblastoid cell lines established from affected heterozygotes, who had mutations of either G88C or G209A alleles, with a severe clinical phenotype.…”
Section: Snca (α-Synuclein)mentioning
confidence: 79%
“…When translated, these lead to the missense mutations Ala53Thr and Ala30Pro, respectively. Recently, reduced mRNA expression of the G209A allele was reported in a Greek-American family [23]. Very recently, we reported that the mRNA expression of the mutant G88C and G209A alleles of the α-synuclein gene is significantly reduced relative to the wild-type allele in lymphoblastoid cell lines established from affected heterozygotes, who had mutations of either G88C or G209A alleles, with a severe clinical phenotype.…”
Section: Snca (α-Synuclein)mentioning
confidence: 79%
“…Independent reports on other patients [Kobayashi et al, 2003;Markopoulou et al, 1999] have previously shown that expression of the same SNCA allele as well as of the allele for the p.Ala30Pro mutation, was either absent or significantly reduced. This raises the question how common such monoallelic SCNA expression is; studies on this issue will provide important insights, however, they are complicated, because nucleotide variations in the coding sequence of the gene are rare.…”
Section: Discussionmentioning
confidence: 93%
“…Surprisingly, the p.Ala53Thr and p.Ala30Pro alleles were found to be silenced to different degrees, compared to the expression of the normal counterpart in the same patient, in various cases [Kobayashi et al, 2003;Markopoulou et al, 1999]. This interallelic variation of expression, unexpected on the basis of the nature of these mutations, could cause a decrease in alphasynuclein protein in these patients and lead the authors to conclude that a haploinsufficiency effect exists associated with the clinical severity of the disease.…”
Section: Introductionmentioning
confidence: 94%
“…Posttranscriptional regulation of a-synuclein can also occur through endogenous micro RNAs, which bind to the 3 0 end of the gene (Junn et al 2009;Doxakis 2010). A particularly interesting twist to the effects of familial point mutations in SNCA has been provided by a series of studies that, somewhat counterintuitively, suggest that the expression of the mutant alleles is suppressed, especially in cases with prolonged disease (Markopoulou et al 1999;Kobayashi et al 2003), through a mechanism that may involve histone modifications (Voutsinas et al 2010). Remarkably, Voutsinas et al (2010) found that the WT allele is induced in a compensatory fashion, and that the total level of SNCA messenger RNA (mRNA) exceeds that of controls, suggesting that total SNCA levels, rather than the presence of the A53T mutant, are responsible for the disease in these cases.…”
Section: Gain-of-function and Accumulation Of A-synucleinmentioning
confidence: 99%